2012
DOI: 10.1530/eje-11-1017
|View full text |Cite
|
Sign up to set email alerts
|

Risk of elevated resting heart rate on the development of type 2 diabetes in patients with clinically manifest vascular diseases

Abstract: Objective: Sympathetic nerve activation is causally related to insulin resistance as both a cause and a consequence. Resting heart rate (RHR) reflects sympathetic nerve activity. We investigated the effect of RHR on the incidence of type 2 diabetes mellitus (T2DM) in patients with clinically manifest vascular diseases. Design: Data were used from the second manifestations of arterial disease (SMART) study: a prospective cohort study of patients with clinically manifest vascular diseases (nZ3646). Methods: RHR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 41 publications
3
21
0
Order By: Relevance
“…These results are in keeping with previous evidence showing that heart rate is predictive of type 2 diabetes in the general population (2,3,4,5,20). However, the precise nature of the pathophysiological relationship underlying the increased risk of hyperglycaemia in those with an elevated heart rate has not been explained.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results are in keeping with previous evidence showing that heart rate is predictive of type 2 diabetes in the general population (2,3,4,5,20). However, the precise nature of the pathophysiological relationship underlying the increased risk of hyperglycaemia in those with an elevated heart rate has not been explained.…”
Section: Discussionsupporting
confidence: 89%
“…Elevated heart rate has been associated with an increased risk of type 2 diabetes in a number of epidemiological studies (1,2,3,4,5). This association has been mainly attributed to increased insulin resistance, secondary to the activation of sympathetic nerve activity (6,7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, the association between elevated resting heart rate and type 2 diabetes remains unclear (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Some studies suggested an increased risk of type 2 diabetes with higher heart rate (6;7;10;12-17), whereas others found the association to be no longer significant after adjustment for potential confounding factors (8;9;11).…”
Section: Introductionmentioning
confidence: 99%
“…RHR is positively associated with sub-clinical inflammation and increased RHR may also be a sign of sub-clinical heart disease [9]. It is reported that insulin resistance and elevated sympathetic nerve activity are closely linked with each other [10]. Acute reflex activation of the sympathetic nerve system could induce acute insulin resistance in humans [10].…”
Section: Introductionmentioning
confidence: 99%
“…Acute reflex activation of the sympathetic nerve system could induce acute insulin resistance in humans [10]. Moreover, chronically increased sympathetic nerve activity can precede the development of insulin resistance and obesity [10,11].…”
Section: Introductionmentioning
confidence: 99%